Seeds Quality and Quantity of Soybean [Glycine max (L.) Merr.] Cultivars in Response to Cold Stress - Staniak, Mariola; Stępień-Warda, Anna; Czopek, Katarzyna; Kocira, Anna; Baca, Edyta (Agronomy (Basel), 2021)
The aim of the study was to identify the response to cold stress of 16 soybean cultivars by evaluating their emergence, yield level, and seed chemical composition. Studies were conducted in 2018–2019. A total of sixteen soybean cultivars belonging to three earliness groups (early, medium-early and late) were included. Short-term (3-day) cold stress (12/6 °C day/night) was applied immediately after sowing (A), 3 days (B) and 6 days (C) after sowing seeds, while long (9-day) cold stress (D) was applied immediately after sowing seeds. In the control plot (K), plants were grown under optimum conditions (20/15 °C day/night). The study showed that cold stress, reduced plant emergence by 5–10%, depending on the treatment. Long stress (D) had a beneficial effect on the yield of all soybean cultivars (average yield increase of 21.5%), with statistically significant differences in 12 cultivars and a trend in four cultivars. Short stress also caused a significant increase in yield on treatments B and C (by 6.8 and 11.6%, respectively). Cold stress did not significantly affect the nutrient content of seed yield. Varietal differentiation was found with respect to yield and chemical composition of seeds.